2017
DOI: 10.1186/s40463-017-0242-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety of transtympanic application of probiotics in a chinchilla animal model

Abstract: BackgroundChronic suppurative otitis media can be recalcitrant and difficult to treat, particularly with the increasing occurrence of antibiotic resistance. Lactobacillus plantarum is a probiotic that has been shown to decrease S. aureus and P. aeruginosa growth in wounds, making it a good candidate for the treatment of chronic suppurative otitis media. However, before it can be applied in the ear, its ototoxicity potential must be evaluated.MethodsA prospective controlled trial was conducted in a chinchilla a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this regard, in a study on patients with second and 3rd-degree burn wounds, Peral et al (2019) showed that dermal treatment with L. plantarum may reduce the bacterial count in the wounds [31] . Also, Carol Nhan et al (2017) indicated that L. plantarum could reduce the S. aureus and P. aeruginosa growth in the wounds [32] . Moreover, the use of lactic acid bacteria as probiotic may accelerate wound healing process and reduce infection by different mechanisms [29] .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in a study on patients with second and 3rd-degree burn wounds, Peral et al (2019) showed that dermal treatment with L. plantarum may reduce the bacterial count in the wounds [31] . Also, Carol Nhan et al (2017) indicated that L. plantarum could reduce the S. aureus and P. aeruginosa growth in the wounds [32] . Moreover, the use of lactic acid bacteria as probiotic may accelerate wound healing process and reduce infection by different mechanisms [29] .…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to antibiotics, research is being carried out on the possibility of using pharmaceutical preparations based on silver such as Silver Chloride Gel [2] and Argentum Quartz (R) [3], probiotics such as Lactobacillus plantarum [4], Curcumin oile [5] and new types of bandages, for example the Lawsonia Inermisgelatin-starch nano-fibrous bandage [6]. However, these methods are only for topical use and do not have a systemic effect, so they does not act upon the site of chronic infection (which often forms after the biofilm formation), and also does not affect the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…There is recent research in advanced treatment methods of inflammatory and purulent processes. The use of silver [2,3], probiotics [4], curcumin oil [5] preparations and new wound dressing [6] in the treatment of suppurative wounds is being investigated. However, this is a topical wound therapy.…”
Section: Introductionmentioning
confidence: 99%